2019
DOI: 10.1186/s13071-019-3590-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of the major arboviral vector Aedes aegypti in urban drain-water and associated pyrethroid insecticide resistance is a potential global health challenge

Abstract: Background Aedes aegypti were found developing in the water in open public drains (drain-water, DW) in Jaffna city in northern Sri Lanka, a location where the arboviral diseases dengue and chikungunya are endemic. Methods Susceptibilities to the common insecticides dichlorodiphenyltrichloroethane (DDT), malathion, propoxur, permethrin and deltamethrin and activities of the insecticide-detoxifying enzymes carboxylesterase (EST), glutathione S-transferase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 32 publications
(41 reference statements)
0
18
0
Order By: Relevance
“…Resistance to commonly used insecticides has been investigated in brackish water breeding as well as in drain-water breeding Ae aegypti mosquitoes in Sri Lanka [24,25]. Drain-water breeding mosquitoes were reported to be resistant to pyrethroids (deltamethrin and permethrin) and to show higher GST and MO activities [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resistance to commonly used insecticides has been investigated in brackish water breeding as well as in drain-water breeding Ae aegypti mosquitoes in Sri Lanka [24,25]. Drain-water breeding mosquitoes were reported to be resistant to pyrethroids (deltamethrin and permethrin) and to show higher GST and MO activities [24].…”
Section: Discussionmentioning
confidence: 99%
“…A study analyzing the susceptible status of the drain-dwelling Ae. aegypti in Sri Lanka reported that mosquitoes with elevated activities of GST and monooxygenases were resistant to pyrethroids, malathion and propoxur [24]. Aedes aegypti collected from brackish water breeding sites were reported as resistant to propoxur (0.1%), whereas no significant differences were observed when these brackish water breeders were compared with fresh water breeders for permethrin (0.25%) and malathion (4%) [25].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The ability of Ae. aegypti to develop in polluted water in surface drains in Jaffna city is associated with greater resistance to pyrethroids [43]. Elucidating biological changes in anophelines associated with similar adaptation to salinity and pollution in Jaffna city can further help understand the adaptability of different mosquitoes to anthropogenic environmental changes.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to deltamethrin in Ae. aegypti developing in polluted drain water in Jaffna city was suggested to be caused by adaptation to cope with organic pollutants in drain water and possibly the common use of pyrethroids to control adult mosquitoes and other insect pests in Jaffna [43]. The same factors may also be responsible for deltamethrin resistance in Jaffna city anophelines.…”
Section: Discussionmentioning
confidence: 99%